(untitled) (Archaeologia Adriatica, 2012)
The objective of this paper is to review the history of terminology supporting the scientific disciplines of underwater/submarine, maritime and nautical archaeology within the framework of Croatian archaeology, and provide recommendations for future classifications. Underwater archaeology and submarine archaeology are generally accepted technical terms denoting archaeological research conducted under special conditions, and requiring appropriate equipment and tools. Proper definition of terms nautical and maritime archaeology makes it possible to differentiate between the tasks and objectives of the two disciplines and clarify their scientific contributions to archaeology in general, providing a much clearer perception of their content and meaning.